ANALISIS KEAMANAN LOGIN ROUTER MIKROTIK DARI SERANGAN BRUTEFORCE MENGGUNAKAN METODE PENETRATION TESTING (Studi Kasus: SMK NEGERI 2 SUMBAWA) - Yudi Mulyanto; Akbar Algi Fari (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The development of network technology from time to time is growing rapidly, therefore, a secure network access is needed. With so many accesses to the network, there will also be many opportunities for crime to occur within the network. This study uses the penetration testing method which aims to analyze security loopholes at the login from the Mikrotik router at SMKN 2 Sumbawa. In carrying out attack trials, this study uses Brute Force. The results of the study found security holes on the Mikrotik Router login page that can be attacked using Brute Force, as evidenced by getting the login username and password from the Mikrotik Router. The final result in the research provides a solution on how to prevent Brute Force attacks to be considered for Network admins in securing Routers